Melphalan delivery and co-delivery nanoformulations for cancer therapy: A comprehensive review - Hamidreza Abdouss; Arezoo Gholami; Mehrab Pourmadadi; Payam Zahedi; Majid Abdouss; Abbas Rahdar; Sadanand Pandey (European Journal of Medicinal Chemistry Reports)
Regardless of the area or the socio-economic status, cancer is currently the second or third prevalent cause of mortality ahead of stroke and coronary heart disease. Melphalan anticancer medication is the phenylalanine derivative of nitrogen mustard and has been demonstrated to successfully treat various types of cancers by suppressing the synthesis of deoxyribonucleic acid. Moreover, melphalan has been shown to exhibit synergetic effects in the treatment of multidrug-resistant tumors. However, its clinical application is restricted since it comes with severe adverse effects and significant drawbacks, such as non-target selectivity and short plasma half-life. To circumvent these constraints, various nanotechnological delivery platforms have been designed in recent years with the goal of improving melphalan delivery to tumor sites and regulating the EPR effect. This review article provides an overview of melphalan-based drug delivery systems (DDS), which include polymeric, lipid-based, and inorganic nanoformulations. The principal objective of this paper is to discuss the latest progress of the developed melphalan delivery systems and compare their essential factors such as particle size, size distribution, release profile, zeta potential, encapsulation and loading efficiency, and in vitro and in vivo assessments. Additionally, different platforms for the co-delivery of melphalan with other drugs have been reviewed, which provide promising future possibilities for cancer treatment. The information summarized in this context will contribute to developing a more practical approach for the future of cancer treatment.